DAMES EMPLOYÉES AT THE SUEZ CANAL COMPANY: THE "EGYPTIANIZATION" OF FEMALE OFFICE WORKERS, 1941–56. (18th July 2014) - Curli, Barbara
Abstract The article is a case study of work organization at the Services d'Egypte of the Suez Canal Company from the outbreak of World War II to the company's nationalization in 1956. In this multinational and multicultural workplace, organizational hierarchies and division of labor were traditionally defined according to "national" identities, while maintaining a strict segregation between européens and indigènes, to use the company's terminology. Starting in the 1930s, the company faced new measures of economic nationalism imposed by the Egyptian government, including required quotas of Egyptian personnel. These measures progressively redefined the political boundaries of the company's action in the management of its workforce. Using unpublished archival documents from the company's personnel files, this article analyzes the processes of feminization and Egyptianization of the company's office workers during World War II and the 1950s. The process was driven by a precise organizational strategy, based on both "racial" and "gender" criteria, which aimed to redefine the company's internal hierarchies and to keep management and decision making in the hands of the "Europeans, " while complying with the terms of the conventions of 1937 and 1949 that regulated the relationship between the company and the Egyptian government.